2009
DOI: 10.1002/nau.20847
|View full text |Cite
|
Sign up to set email alerts
|

Bladder pain syndrome international consultation on incontinence

Abstract: Aims of Study:The Bladder Pain Syndrome Committee of the International Consultation on Incontinence was assigned the task by the consultation of reviewing the syndrome, formerly known as interstitial cystitis, in a comprehensive fashion. This included the topics of definition, nomenclature, taxonomy, epidemiology, etiology, pathology, diagnosis, symptom scales, outcome assessment, principles of management, specific therapies, and future directions in research. Study Design, Materials, Methods: The emphasis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(140 citation statements)
references
References 56 publications
3
126
0
11
Order By: Relevance
“…Interstitial cystitis (IC) is a chronic non-inflammatory disease especially with irritative urinary symptoms, mostly on women [15]. The Society of Urodynamics, Female Pelvic Medicine, and Urogenital Reconstruction (SUFU) defined IC as "an unpleasant sensation (pain, pressure, discomfort) perceived to be related to the urinary bladder, associated with lower urinary tract symptoms of more than 6 weeks duration, in the absence of infection or other identifiable causes" [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interstitial cystitis (IC) is a chronic non-inflammatory disease especially with irritative urinary symptoms, mostly on women [15]. The Society of Urodynamics, Female Pelvic Medicine, and Urogenital Reconstruction (SUFU) defined IC as "an unpleasant sensation (pain, pressure, discomfort) perceived to be related to the urinary bladder, associated with lower urinary tract symptoms of more than 6 weeks duration, in the absence of infection or other identifiable causes" [16].…”
Section: Discussionmentioning
confidence: 99%
“…PRP contains many growth factors and proteins, such as platelet-derived growth factors (PGDF), transforming growth factor beta (TGF-β), fibroblast growth factor (FGF), insulin-like growth factor 1(IGF-1), connective tissue growth factor (CTGF) and epidermal growth factor (EGF) [12,13]. These factors that are present in PRP promote accelerated repair with better tissue differentiation at the area of the injury [15].…”
mentioning
confidence: 99%
“…Moreover, unlike previous studies, the technique employed in this study showed that the reduction in urinary GAG excretion in patients with PBS/IC occurred uniformly, with no predilection for any urinary GAG. Our study was not managed to analyze urinary GAG and the activity of the disease, such as degree of symptoms, glomerulation and histologic findings since they are not reliable isolated markers today (29). As for the HA, although the average urinary concentration was lower in the PBS/IC group but there was no significant difference when compared to control.…”
Section: Discussionmentioning
confidence: 95%
“…1 BPS mainly affects adult females; however, it can occur at any age. The female to male ratio is >5:1.…”
Section: Wwwtrendsinmenshealthcom Trends In Urology and Men's Health mentioning
confidence: 99%